Enantioselective Dearomative Alkynylation of Chromanones: Opportunities and Obstacles - Guan, Yong; Buivydas, Tadas; Lalisse, Remy F.; Ali, Rameez; Hadad, Christopher M.; Mattson, Anita E. (Synthesis, 2022)
A catalytic and highly enantioselective dearomative alkynylation of chromanones has been discovered that enables the construction of biologically relevant tertiary ether stereogenic centers. This methodology is robust, accommodating a variety of alkynes and chromanones. More than 40 substrates tested gave rise to >90% ee. Computational studies have indicated that the optimal indanyl ligand identified for most cases likely affords a network of supportive, non-covalent interactions that drive the enantioselective nature of the reaction.
Keywords: tertiary ether stereocenter; benzopyrylium triflate; bis(oxaolines); alkynes; copper